FAITH-BASED COUNSELING AS AN ALTERNATIVE TO RESTORING ADOLESCENT AFFECTION CONDITIONS AFTER EXPERIENCING PARENTAL DIVORCE - MUHAMMAD FERDIANSYAH; MUHAMMAD ZULFIKAR; AFFAN YUSRA; MUHAMMAD ALRIDHO LUBIS; FREDDI SARMAN; Muhammad Alridho Lubis (Universitas Islam Negeri Mataram, 2022)
The purpose of this study is to examine the picture of adolescent affection conditions after parents experience divorce. This type of research is qualitative research with a case study type. Data collection techniques use interview observation instruments and documentation. Data is obtained through students, kindergarten teachers, homeroom teachers, subject teachers, parents, and peers. The validity test uses our criteria, namely (1) Trust test (2) Transferability test, (3) Dependability test, and (4) Conformity test. Furthermore, the data obtained during the process in the field is continuously analyzed which refers to the Miles and Huberman model. The results showed that the condition of adolescent affection subjects